Characterization of acute stress reaction following an IED blast-related mild traumatic brain injury. (8th May 2015) - Norris, Jacob N.; Smith, Scottie; Harris, Erica; Labrie, David Walter; Ahlers, Stephen T.
Abstract: Primary objective : To characterize an acute stress reaction (ASR) following an improvised explosive device (IED) blast-related mild traumatic brain injury (mTBI). Research design : Participants were male, US military personnel treated in Afghanistan within 4 days following an IED-related mTBI event ( n = 239). Methods and procedures : Demographics, diagnosis of ASR, injury history and self-reported mTBIs, blast exposures and psychological health histories were recorded. Main outcomes and results : In total, 12.5% of patients met ASR criteria. Patients with ASR were significantly younger and junior in rank ( p < 0.05). Patients with ASR were more likely to experience the IED-blast while dismounted, report a loss of consciousness (LOC) and higher pain levels ( p < 0.05). Adjusting for age and rank, multivariate logistic regression showed an association between mTBI history and ASR (AOR = 1.405; 95% CI = 1.105–1.786, p < 0.01). Adjusting for mechanism of injury (dismounted vs. mounted), LOC and pain, multivariate logistic regression showed an association between mTBI history and ASR (AOR = 1.453; 95% CI = 1.132–1.864, p < 0.01). Prior blast exposure and past psychological health issues were not associated with ASR. Conclusions : A history of multiple mTBIs is associated with increased risk of ASR. Future research is warranted.